Pengaruh Stres Kerja terhadap Turnover intention dengan Kepuasan Kerja sebagai Variabel Mediasi (Studi Kasus di PT. Victory International Futures Yogyakarta) - Mitha Indri Pratiwi; Muhammad Roni indarto (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2022)
This research aims to analyze the effect of work stress on turnover intention with job satisfaction as an intervening variable. The sample in this research are employees of PT. Victory International Futures Yogyakarta. The sampling technique used in this research is the nonprobability sampling technique. The method used is saturated sampling method with a total of 69 respondents. Data analysis used multiple linear regression analysis using the IBM SPSS Statistics 25 Program. The results showed that work stress has a positive effect on job satisfaction, work stress has a positive effect on turnover intention, job satisfaction has a negative effect on turnover intention and job satisfaction cannot mediate between variables work stress on turnover intention variable